UPAYA PENINGKATAN CITRA KAWASAN WISATA BUDAYA PADA SANGGRALOKA SEKAR WILIS PONOROGO - Eva Elviana; Erwin Djuni Winarto; Azkia Avenzoar (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
Sanggraloka Sekar Wilis is the name of a tourist area located in the village of Kesugihan, Pulung District, Ponorogo. With a tread location on the slopes of Mount Wilis, with a hilly background, it provides a beautiful natural panorama, supported by various kinds of trees as shade and a source of clean water which is used as a family swimming pool. The existence of several children's play facilities, as well as a campsite, makes this place visited by many local people. Although there is a Pendopo building with the Joglo Panoragan style in this area, the area's image that reflects the Ponorogo art and culture, has not been adequately provided. Cultural attractions, such as the Reog Ponorogo dance performance, are performed in an open space that is still quite wide. This study aims to make efforts to improve the image of the area as cultural tourism, through exploration of architectural elements so as to improve the image of the area by raising vernacular values. This qualitative research uses descriptive analysis methods through field observations and in-depth interviews. The results showed that the use of vernacular architecture in the completion of the building could improve the image of the tourist area, thereby strengthening the Ponorogo cultural identity.